Population-Attributable Risk of Adverse Childhood Experiences for High Suicide Risk, Psychiatric Admissions, and Recurrent Depression, in Depressed Outpatients [抑郁门诊患者的童年期不良经历对于高自杀风险, 精神病性住院和复发性抑郁的人群归因危险度] [Riesgo Atribuible Poblacional de Experiencias Adversas Infantiles Para Alto Riesgo Suicida, Hospitalizaciones Psiquiátricas, y Depresión Recurrente, en Pacientes Deprimidos Ambulatorios] - Martinez-Diaz, P (Taylor and Francis Ltd., 2021)
Background: Population-attributable risk (PAR) may help estimate the potential contribution of adverse childhood experiences (ACEs) to serious clinical presentations of depression, characterized by suicidality, previous psychiatric admissions, and episode recurrence. Objective: To determine the PAR of ACEs for serious clinical presentations of depression (high suicide risk, previous psychiatric admissions, and recurrent depression) in outpatients with ICD-10 clinical depression. Method: Systematic chart review of 1,013 adults who were assessed and/or treated in a mental health clinic in Santiago, Chile for a major depressive episode. Data were collected on demographics and clinical characteristics of depression. Exposure to ACEs was determined with the Brief Physical and Sexual Abuse Questionnaire, assessing seven types of ACEs. Multivariable logistic regression analysis was used to assess the association between exposure to ACEs and suicidality, previous psychiatric admissions, and recurrence. Predicted probabilities were used for calculations of PAR. Results: Of the 1,001 study participants with complete data, 53.3% had recurrent depression, 13.5% had high suicide risk, and 5.0% had previous psychiatric admissions. Exposure to at least one ACE was recorded for 69.0% of the sample. Exposure to at least one ACE and specific types of ACEs (i.e. childhood sexual abuse and traumatic separation from caregiver) were associated with serious clinical presentations of depression. A dose-response relationship was observed between cumulative exposure to ACEs and the most serious clinical presentations of depression. ACEs were attributed to a significant proportion of disease: 61.6% of previous psychiatric admissions, 45.0% of high suicide risk, and 14.5% of recurrent depression. Conclusions: A substantial proportion of serious clinical presentations of depression among outpatients are associated with ACEs. Early detection of depressive episodes associated with ACEs, and tailored treatment for these patients, may potentially reduce the incidence of serious complications in this population. © 2021 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.